Proceedings of the International Conference on Science and Education and Technology 2018 (ISET 2018) 2018
DOI: 10.2991/iset-18.2018.61
|View full text |Cite
|
Sign up to set email alerts
|

The Dimensions of Soft Skills and CBT (Competency Based Training) on the Entrepreneurship Education in Agribusiness Vocational High School

Abstract: The problems of low level care and consistency on entrepreneurship education cause distortion in building students' entrepreneurship spirit. Identification of soft skills and CBT dimension is needed as the basic analysis in improving the effectiveness of entrepreneurship education. The purpose of this research was to understand the types of soft skills, the applied CBT concept, the involved actors, and the learning process. The methods used in this research were observation, interview, and documentation. Meanw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
2
3
0
Order By: Relevance
“…The fact that the welding workshop of PVHS 2 of Tulungagung does not open every day and is run only to order means that the production unit has not been managed professionally and has not taken the priority of the school. This supports the finding of the research by Marliyah (2018) stating that irregular activities of production units at VHS are indicative of the fact that they have not taken the priority of the school. Based on the interviews, there were some obstacles in running the welding workshop of PVHS 2 of Tulungagung, one of which was the product marketing process.…”
Section: Alumni Taking Entrepreneurial Actionssupporting
confidence: 89%
See 2 more Smart Citations
“…The fact that the welding workshop of PVHS 2 of Tulungagung does not open every day and is run only to order means that the production unit has not been managed professionally and has not taken the priority of the school. This supports the finding of the research by Marliyah (2018) stating that irregular activities of production units at VHS are indicative of the fact that they have not taken the priority of the school. Based on the interviews, there were some obstacles in running the welding workshop of PVHS 2 of Tulungagung, one of which was the product marketing process.…”
Section: Alumni Taking Entrepreneurial Actionssupporting
confidence: 89%
“…This is in line with the result of Rokhimah & Margunani (2017) stating that entrepreneurship education positively affects students' entrepreneurial spirit. Entrepreneurship education is a learning process through which to change students' attitude towards entrepreneurship as a career choice (Marliyah, 2018). PVHS 2 of Tulungagung provides entrepreneurship both in theory and in practice through students' activities in production units conducted to enhance students' entrpreneurial skills.…”
Section: Alumni Taking Entrepreneurial Actionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The low learning process of entrepreneurship subjects in schools in Pekanbaru is also in line with several learning study results in Indonesia (World Bank, 2018;PISA 2000PISA -2018Kurniawati et al, 2018;Center for Educational Assessment, 2018;ACDP, 2014;Center for Educational Assessment, 2016;and INNOVATION, 2018) which shows that the quality of the learning process is still less reliable. In addition, it is also in line with the results of research by Marliyah et al (2018), which revealed that the learning process in schools has not been optimally effective in improving student learning outcomes (Marliyah et al, 2018). The implementation of the learning evaluation of entrepreneurship subjects is still relatively unoptimal; the average of the two public and private schools is only 2.89.…”
Section: Discussionsupporting
confidence: 62%
“…Entrepreneurial education must build the best beliefs, motivations, intentions, and grit to cope with a loss to succeed and win again, exceeding the focus of other companies (Welsh et al, 2016). Entrepreneurial education's performance is the responsibility of entrepreneurial lecturers and the importance of teamwork in learning preparation, delivery, and assessment, stressing qualitative and comprehensive methods (Marliyah et al, 2018). The quality of lecturers, according to students, is assessed from the student's view of quality, degree, experience, disposition, and mindset (Ginsburg & Smith, 2014).…”
Section: Discussionmentioning
confidence: 99%